Supervisi Akademik Kepala Sekolah Dan Pengaruhnya Terhadap Mutu Pendidikan - Rica Widiastuty (ALACRITY : Journal of Education, 2022)
The quality of education is a topic of discussion in an education management. The quality of education is an effort that must be done well in order to have quality and relevant educational values ??through the supervision of academic leadership (principals). Academic supervision of leadership has a positive impact on improving the quality of education, in this case empowering educational leadership can improve functional abilities so that school principals can serve according to the authority and responsibility that are able to regulate all school activities so that they can run well and function optimally.